(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study analyzes the influence of Peer to Peer (P2P) Lending use and financial literacy on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Semarang City, with social capital as a mediating variable. Using a quantitative approach, 100 MSME owners were selected through purposive sampling. Data were collected via questionnaires and analyzed using the SEM-PLS method with SmartPLS 3.0. Results show that financial literacy (p=0.000) and social capital (p=0.006) significantly and positively affect financial performance. Social capital partially mediates the relationship between financial literacy and financial performance, with a significant indirect effect (p=0.012). Conversely, P2P lending use does not significantly affect financial performance either directly (p=0.221) or indirectly through social capital. The study concludes that financial literacy is crucial for improving MSME financial performance, and its impact is strengthened by social capital. The effectiveness of tools like P2P lending depends on the entrepreneur’s prior financial acumen.